Peranan Lembaga Keuangan Syariah dalam Mengimplementasikan Keuangan Inklusif (Studi pada BMT Marwah dan Badan Amil Zakat Nasional (BAZANAS) Kabupaten Kampar) - Mifta Husada (ISLAMIC BUSINESS and FINANCE (IBF), 2021)
The financial system has a very important role in the growth and stability of a country's economy. Increasing access to financial institutions for the public is required in order to achieve economic growth and a stable financial system. By changing an exclusive financial system into an inclusive financial system, it is hoped that people in the group in the bottom of the pyramid, most of whom are not covered by formal financial access, can use and take advantage of formal financial services. Baitul Mal wat Tamwil (BMT) and the Zakat Institution are inclusive Islamic financial institutions. The research was conducted in Kampar Regency and is a qualitative research. In Kampar District BMT Marwah and BAZNAS are sharia financial institutions that directly touch the lower class society. The formulation of the problem in this study is the efforts of BMT Marwah and BAZNAS of Kampar Regency in implementing financial inclusion as well as what are the obstacles and solutions in implementing inclusive finance. The results of this research are that BMT Marwah provides financial products according to the needs of the community, easy requirements, clarity in recording every transaction and the existence of services with a ball pick-up system that makes it easy for the community and BMT Marwah can directly socialize with customers or prospective customers. In an effort to realize inclusive zakat, BAZNAS Kampar Regency makes it easy for muzakki with zakat pick-up services atat muzakki to transfer to a predetermined account, while to increase the number of muzakki BAZNAS Kampar Regency continues to socialize and educate zakat and the formation of UPZ. The obstacle encountered in the field for BMT Marwah is the character of the community which is quite difficult to resolve mudharabah financing. BAZNAS Kampar Regency in running its operations is constrained by limited funds and the quality of amil is not yet capable of carrying out its duties, because there is no training and regular guidance for amil.